Heavy metal adsorption slow-release fertilizer as well as preparation method and application thereof

By growing cyclodextrin metal organic framework compounds in situ in polyvinyl alcohol (PVA), combining the chelation coordination of potassium ions, forming a porous structure of cyclodextrin metal organic framework, the problems of water resistance and poor strength of existing PVA slow-release fertilizers are solved, efficient utilization and sustained release of chemical fertilizers are achieved, pollution and heavy metal enrichment are reduced, and environmentally friendly agricultural development is promoted.

CN119874444APending Publication Date: 2025-04-25CHINA NAT TOBACCO QUALITY SUPERVISION & TEST CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887994.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-25

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a heavy metal adsorption slow release fertilizer and a preparation method and application thereof.The slow release fertilizer is composed of polyvinyl alcohol (PVA) and a cyclodextrin metal organic framework compound growing on the polyvinyl alcohol (PVA) in situ, and the cyclodextrin metal organic framework compound is composed of a complex formed by cyclodextrin and metal ions, a hydrogen bond is formed between the polyvinyl alcohol and the cyclodextrin metal organic framework compound. The heavy metal adsorption slow-release fertilizer disclosed by the invention is high in chemical fertilizer utilization rate, proper in release speed and less in pollution, and can realize a slow-release effect of a mixed water-soluble fertilizer in a plant growth cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fertilizers, and in particular to a heavy metal adsorption slow-release fertilizer and a preparation method and application thereof, and in particular to a heavy metal adsorption slow-release fertilizer having a cyclodextrin metal organic framework compound and a preparation method and application thereof. Background Art

[0002] Most of the slow-release fertilizers currently used in agriculture require coating materials, and most of the coatings are synthetic polymer materials of the polyolefin class, which are difficult to degrade. In order to reduce the pollution of coating materials to the environment, many researchers have begun to pay attention to renewable materials. Polyvinyl alcohol (PVA) is a water-soluble polymer that can be decomposed into carbon dioxide and water by microorganisms. It is a new generation of environmentally friendly new slow-release materials that can be fully incorporated into the material circulation system of nature and will not cause harm to the ecological environment. However, due to the presence of a large number of -OH in the molecular structure, PVA has high hygroscopicity and poor water resistance. In the process of slow-release fertilizer coating, due to poor water resistance and strength, a large concentration of chemical fertilizer is applied in the initial stage of application. In addition, this type of slow-release fertilizer easily causes crops to absorb excessive nutrients, resulting in seedling burn, which not only wastes fertilizers but also is not conducive to crop growth. This greatly limits its application in the agricultural field. Summary of the invention

[0003] In order to overcome the defects of the existing PVA slow-release fertilizer, the present invention provides a heavy metal adsorption slow-release fertilizer and a preparation method thereof. The heavy metal adsorption slow-release fertilizer of the present invention has high fertilizer utilization rate, suitable release speed, less pollution, and can achieve the slow-release effect of mixed water-soluble fertilizer during the plant growth cycle. In addition, the heavy metal adsorption slow-release fertilizer of the present invention plays a positive role in adsorbing heavy metal cadmium in the soil, reducing the enrichment of heavy metals in plants.

[0004] The present invention is achieved by adopting the following technical solutions.

[0005] On the one hand, the present invention provides a heavy metal adsorption slow-release fertilizer, which is composed of polyvinyl alcohol (PVA) and a cyclodextrin metal skeleton compound in situ grown on the polyvinyl alcohol (PVA), wherein the cyclodextrin metal skeleton compound is composed of a complex formed by cyclodextrin and metal ions, and hydrogen bonds are formed between the polyvinyl alcohol and the cyclodextrin metal skeleton compound.

[0006] Preferably, the mass ratio between the polyvinyl alcohol and the cyclodextrin in the cyclodextrin metal framework compound is 100:5-15.

[0007] Preferably, the cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin (γ-CD).

[0008] Preferably, the metal ion is a potassium ion.

[0009] The heavy metal adsorption slow-release fertilizer of the present invention adopts the unique water solubility of polyvinyl alcohol (PVA) and cyclodextrin metal-organic framework (Metal-Organic Framework, MOF) compounds, and forms nucleation sites of CD-MOF crystals in a mixed solution of water-soluble fertilizer and PVA. By controlling the reaction conditions, porous CD-MOFs with heavy metal adsorption capacity are formed in situ in the mixed solution of water-soluble fertilizer and PVA. By adding water-soluble fertilizer containing potassium fertilizer to PVA, the potassium ions in the potassium fertilizer can be used as inorganic metal centers, and cyclodextrin is added as an organic ligand to form a new PVA multifunctional slow-release fertilizer material having a porous structure cyclodextrin-metal organic framework compound and PVA as a slow-release fertilizer carrier.

[0010] In another aspect, the present invention provides a method for preparing a heavy metal adsorption slow-release fertilizer, the method comprising the following steps:

[0011] Step 1, dissolving water-soluble fertilizer and polyvinyl alcohol (PVA) in deionized water until they are completely dissolved to obtain a mixed aqueous solution of polyvinyl alcohol (PVA) containing water-soluble fertilizer;

[0012] Step 2, dissolving cyclodextrin (e.g., γ-CD) in deionized water until it is completely dissolved to obtain a cyclodextrin aqueous solution;

[0013] Step 3, mixing the solutions obtained in step 1 and step 2, introducing methanol vapor to react, and forming a cyclodextrin metal-organic framework compound; then, adding a surfactant, stirring evenly, standing overnight, centrifuging, removing unreacted supernatant, and obtaining a viscous liquid; step 4, drying the viscous liquid obtained in step 3.

[0014] Preferably, in step 1, the water-soluble fertilizer is 10-30 parts, and the PVA is 100 parts by weight;

[0015] Preferably, in step 1, the water-soluble fertilizer is 10-20 parts, and the PVA is 100 parts by weight;

[0016] Preferably, in step 1, the temperature of the deionized water is 60-80°C.

[0017] Preferably, step 1 also includes adjusting the pH value of the polyethylene (PVA) mixed aqueous solution containing water-soluble fertilizer to 4-6.

[0018] Preferably, in step 1, the water-soluble fertilizer is a mixed fertilizer of potash fertilizer and one or more fertilizers selected from fulvic acid, amino acid, humic acid, and alginic acid.

[0019] Preferably, the potash fertilizer is selected from one or more of potassium nitrate, potassium sulfate, potassium dihydrogen phosphate, potassium chloride, potassium humate and amino acid potassium.

[0020] Preferably, the mass ratio of the potash fertilizer to the one or more fertilizers selected from fulvic acid, amino acids, humic acid, and alginic acid is 1:0-5 parts.

[0021] Preferably, in step 1, the mass fraction of the PVA in water is 15-30%, preferably 17-25%.

[0022] Preferably, in step 1, the viscosity of the PVA is less than or equal to 32 mPa.s.

[0023] Preferably, in step 1, the degree of polymerization of the PVA is 1700-2500.

[0024] Preferably, in step 1, the hydrolysis degree of the PVA is 78-88%.

[0025] Preferably, in step 2, the cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin (γ-CD). Preferably, in step 2, relative to the mass fraction of polyvinyl alcohol PVA in step 1, the cyclodextrin (such as γ-CD) is 5-15 parts, preferably 10-15 parts.

[0026] Preferably, in step 2, the temperature of the deionized water is 60-80° C., preferably 60° C. Preferably, in step 3, the amount of the surfactant added is 0.5-1 part relative to the mass fraction of the polyvinyl alcohol PVA in step 1;

[0027] Preferably, in step 3, the centrifugal speed is 2000-3000 r / min;

[0028] Preferably, in step 3, the surfactant is a cationic surfactant selected from one or more of hexadecyltrimethylammonium bromide, hexadecylpolyoxyethylene ether dimethyloctyl ammonium chloride, ethylenebis[(octadecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(hexadecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(dodecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(decylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(octylpolyoxyethylene / polyoxypropylene block group) ammonium chloride / (hexadecylpolyoxyethylene / polyoxypropylene block group) ammonium chloride], propylenebis[(hexadecylamidepropyl dimethyl) chloride / ammonium bromide] and propylenebis[(dodecylamidepropyl dimethyl) chloride / ammonium bromide].

[0029] Preferably, in step 4, the drying temperature is 50-80°C.

[0030] In a specific embodiment, the preparation method comprises the following steps:

[0031] Step 1, dissolve 10-30 parts of water-soluble fertilizer and 100 parts of polyvinyl alcohol (PVA) in 60-80°C deionized water, and continue stirring for 1-3 hours until completely dissolved to obtain a mixed aqueous solution of polyvinyl alcohol (PVA) containing water-soluble fertilizer, and adjust the pH value of the aqueous solution to 4-6.

[0032] Step 2, dissolving 10-15 parts of cyclodextrin (e.g., γ-CD) in deionized water, stirring at 60° C. for 30 minutes until completely dissolved, to obtain a cyclodextrin aqueous solution;

[0033] Step 3, mixing the solutions obtained in step 1 and step 2, introducing methanol vapor into the solution at 50°C to diffuse into the solution for reaction for 6 hours to form a cyclodextrin metal-organic framework compound; then, adding 0.500-1 part (500mg-1000mg of surfactant relative to 100g of PVA) of surfactant, ultrasonically stirring evenly, standing overnight, and centrifuging the mixed solution at 2000-3000r / min for multiple times to remove the unreacted supernatant.

[0034] Step 4, repeatedly injecting the lower layer of viscous liquid after centrifugation into a spherical mold with a diameter of 0.2 cm, drying it in a vacuum drying oven at 50-80° C. for 48 hours to remove the solvent, and obtaining the product.

[0035] The heavy metal adsorption slow-release fertilizer of the invention has a cyclodextrin metal-organic skeleton, and the cyclodextrin metal-organic skeleton is in-situ grown in polyvinyl alcohol (PVA).

[0036] In another aspect, the present invention provides an application of the heavy metal adsorption slow-release fertilizer in the field of agricultural planting, especially in tobacco planting.

[0037] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0038] In the present invention, the hydroxyl groups in cyclodextrin and the hydroxyl groups in PVA form a three-dimensional cross-linked structure through a hydrogen bond structure, which can improve the water resistance and strength of PVA, thereby ensuring that PVA can swell in water, absorb and retain a large amount of water, and not dissolve in water. By improving the mechanical strength and chemical stability of PVA, the utilization rate of chemical fertilizers is improved, the release rate of fertilizers can be effectively controlled, the pollution caused by fertilization can be reduced, and the slow release effect of mixed water-soluble fertilizers during the plant growth cycle is achieved.

[0039] The present invention adds potassium fertilizer, wherein the provided potassium ions and cyclodextrin can be chelated and coordinated to form body-centered cubic stacking, and a cyclodextrin metal organic skeleton with a porous structure is formed, which plays a positive role in adsorbing heavy metal cadmium in the soil and reduces the enrichment of heavy metals in plants.

[0040] The invention complies with my country's sustainable development strategy of energy conservation and emission reduction, low-carbon economy and the development plan of vigorously developing biodegradable materials, and is an important direction for the current development of green science and technology and environmental protection.

[0041] The heavy metal adsorption slow-release fertilizer of the present invention has the multi-functions of heavy metal adsorption and fertilizer slow-release, and plays a positive role in developing sustainable and efficient agriculture.

[0042] The hydroxyl groups in the cyclodextrin of the present invention and the hydroxyl groups of PVA form a three-dimensional cross-linked structure through a hydrogen bond structure, thereby improving the water resistance and strength of PVA, thereby ensuring that PVA can swell in water, absorb and retain a large amount of water, and not dissolve in water, and improving the utilization rate of chemical fertilizers by improving the mechanical strength and chemical stability of PVA, effectively controlling the release rate of fertilizers, reducing the pollution caused by fertilization, and realizing the slow release effect of mixed water-soluble fertilizers during the plant growth cycle. In addition, the potassium ions provided by the added potassium fertilizer and the cyclodextrin can be chelated and coordinated, thereby forming a body-centered cubic stacking, and forming a cyclodextrin metal organic skeleton with a pore structure, which plays a positive role in adsorbing heavy metal cadmium in the soil and reducing the enrichment of heavy metals in plants.

[0043] The present invention provides a preparation method and application of a slow-release fertilizer for heavy metal adsorption by a cyclodextrin metal organic framework. A method for in-situ growth of a cyclodextrin metal organic framework in polyvinyl alcohol is provided, wherein potassium ions provided by potassium fertilizer and cyclodextrin can be chelated and coordinated to form a body-centered cubic stacking, and a cyclodextrin metal organic framework with a porous structure is formed, which has an adsorption effect on heavy metal cadmium in the adsorbed soil, and reduces the enrichment of heavy metals in plants. On the other hand, the hydroxyl groups in the cyclodextrin and the hydroxyl groups of PVA form a three-dimensional cross-linked structure through a hydrogen bond structure, and the utilization rate of the fertilizer is improved by improving the mechanical strength and chemical stability of PVA, thereby achieving a slow-release effect of the mixed water-soluble fertilizer during the plant growth cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a SEM image of the heavy metal adsorption slow-release fertilizer of Example 1 of the present invention;

[0045] Figure 2 This is a SEM image of the heavy metal adsorption slow-release fertilizer of Example 4 of the present invention;

[0046] Figure 3 This is a SEM image of the heavy metal adsorption slow-release fertilizer of Example 5 of the present invention;

[0047] Figure 4 It is the SEM picture of the product of Comparative Example 3;

[0048] Figure 5 It is the SEM picture of the product of comparative example 4, wherein Figure 5 A. Figure 5 B. Figure 5 C correspond to products 4A, 4B, and 4C, respectively. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1: Heavy metal adsorption slow-release fertilizer of the present invention

[0051] Preparation method:

[0052] Step 1: dissolve 10 g of amino acid water-soluble fertilizer (commercially available), 5 g of potassium nitrate (commercially available), and 100 g of PVA (117, Kuraray Co., Ltd., Japan) in 500 ml of deionized water at 60° C., stir continuously for 1 hour until completely dissolved, and add acid to adjust the pH of the mixed solution to 6.

[0053] Step 2, completely dissolve 5 g of cyclodextrin (γ-CD) in a deionized water solution, and stir at 60° C. for 30 minutes until completely dissolved.

[0054] Step 3, the solutions of step 1 and step 2 are mixed, the reaction temperature is maintained at 50°C, methanol vapor is continuously introduced into the mixed solution for 6 hours, and then 500 mg of hexadecyltrimethylammonium bromide surfactant is added to the mixed solution, and ultrasonic stirring is performed for 30 minutes. The reaction solution is allowed to stand overnight, and the mixed solution is centrifuged at 3000 r / min twice to remove the unreacted supernatant.

[0055] Step 4: After centrifugation, the lower viscous liquid is injected into a spherical mold with a diameter of 0.2 cm, and dried in a vacuum drying oven at 80°C for 48 hours to remove the solvent. The product of Example 1 is obtained. The SEM image is as follows: Figure 1 shown.

[0056] Example 2: Heavy metal adsorption slow-release fertilizer of the present invention

[0057] Step 1: Dissolve 10g of alginate water-soluble fertilizer (commercially available), 10g of potassium chloride (commercially available), and 100g of PVA (117, Kuraray Co., Ltd., Japan) in 600ml of deionized water at 60°C, stir continuously for 1h until completely dissolved, and add acid to adjust the pH of the mixed solution to 4.5.

[0058] Step 2, completely dissolve 10 g of γ-cyclodextrin (Aladdin) in a deionized water solution, and stir at 60° C. for 30 minutes until completely dissolved.

[0059] Step 3, the solutions of step 1 and step 2 are mixed, the reaction temperature is maintained at 50°C, methanol vapor is continuously introduced into the mixed solution for 6 hours, and then 600 mg of ethylenebis[(hexadecylamidepropyldimethyl)ammonium bromide] (commercially available) surfactant is added to the mixed solution, and ultrasonic stirring is performed for 30 minutes. The reaction solution is allowed to stand overnight, and the mixed solution is centrifuged at 3000 r / min twice to remove the unreacted supernatant.

[0060] Step 4: After centrifugation, the lower viscous liquid is injected into a spherical mold with a diameter of 0.2 cm, and dried in a vacuum drying oven at 80° C. for 48 hours to remove the solvent, thereby obtaining the product of Example 2.

[0061] Example 3: Heavy metal adsorption slow-release fertilizer of the present invention

[0062] Step 1: Dissolve 10g of alginate water-soluble fertilizer (commercially available), 10g of potassium humate (commercially available), and 100g of PVA (117, Kuraray Co., Ltd., Japan) in 700ml of 80°C deionized water, stir continuously for 1h until completely dissolved, and add acid to adjust the pH of the mixed solution to 4.5.

[0063] Step 2, completely dissolve 8 g of γ-cyclodextrin (Aladdin) in a deionized water solution, and stir at 60° C. for 30 minutes until completely dissolved.

[0064] Step 3, the solutions of step 1 and step 2 are mixed, the reaction temperature is maintained at 50°C, methanol vapor is continuously introduced into the mixed solution for 6 hours, and then 600 mg of ethylenebis[(hexadecylamidepropyldimethyl)ammonium bromide] (commercially available) surfactant is added to the mixed solution, and ultrasonic stirring is performed for 30 minutes. The reaction solution is allowed to stand overnight, and the mixed solution is centrifuged at 3000 r / min twice to remove the unreacted supernatant.

[0065] Step 4: After centrifugation, the lower viscous liquid is injected into a spherical mold with a diameter of 0.2 cm, and dried in a vacuum drying oven at 80° C. for 48 hours to remove the solvent, thereby obtaining the product of Example 3.

[0066] Example 4: Heavy metal adsorption slow-release fertilizer of the present invention

[0067] Step 1: Dissolve 10g of alginate water-soluble fertilizer (commercially available), 10g of potassium humate (commercially available), and 100g of PVA (117, Kuraray Co., Ltd., Japan) in 550ml of deionized water at 60°C, stir continuously for 1h until completely dissolved, and add acid to adjust the pH of the mixed solution to 4.5.

[0068] Step 2, completely dissolve 15 g of γ-cyclodextrin (Aladdin) in a deionized water solution, and stir at 60° C. for 30 minutes until completely dissolved.

[0069] Step 3, the solutions of step 1 and step 2 are mixed, the reaction temperature is maintained at 50°C, methanol vapor is continuously introduced into the mixed solution for 6 hours, and then 800 mg of a surfactant, propylene bis[(hexadecylamide propyl dimethyl) ammonium chloride] (commercially available), is added to the mixed solution, and ultrasonic stirring is performed for 30 minutes. The reaction solution is allowed to stand overnight, and the mixed solution is centrifuged twice at 3000 r / min to remove the unreacted supernatant.

[0070] Step 4: After centrifugation, the lower viscous liquid is injected into a spherical mold with a diameter of 0.2 cm, and dried in a vacuum drying oven at 80°C for 48 hours to remove the solvent. The product of Example 4 is obtained. The SEM image is as follows Figure 2 shown.

[0071] Example 5: Heavy metal adsorption slow-release fertilizer of the present invention

[0072] Step 1: Dissolve 15 g potassium chloride (commercially available) and 100 g PVA (117, Kuraray Co., Ltd., Japan) in 500 ml deionized water at 60° C., stir for 1 h until completely dissolved, and add acid to adjust the pH of the mixed solution to 6.

[0073] Step 2, completely dissolve 15 g of cyclodextrin (γ-CD) in a deionized water solution, and stir at 60° C. for 30 minutes until completely dissolved.

[0074] Step 3, the solutions of step 1 and step 2 are mixed, the reaction temperature is maintained at 50°C, methanol vapor is continuously introduced into the mixed solution for 6 hours, and then 1000 mg of hexadecyltrimethylammonium bromide surfactant is added to the mixed solution, and ultrasonic stirring is performed for 30 minutes. The reaction solution is allowed to stand overnight, and the mixed solution is centrifuged twice at 3000 r / min to remove the unreacted supernatant.

[0075] Step 4: After centrifugation, the lower viscous liquid is injected into a spherical mold with a diameter of 0.2 cm, and dried in a vacuum drying oven at 80°C for 48 hours to remove the solvent. The product of Example 5 is obtained. The SEM image is as follows Figure 3 shown.

[0076] Comparative Example 1

[0077] 100g PVA (117, Kuraray Co., Ltd., Japan) was dissolved in 600ml 60°C deionized water, and stirred for 1h until completely dissolved. The viscous liquid was injected into a spherical mold with a diameter of 0.2cm, and dried in a vacuum drying oven at 80°C for 48h to remove the solvent. The product of Comparative Example 1 was obtained.

[0078] Comparative Example 2

[0079] 10g of alginic acid water-soluble fertilizer (commercially available) and 100g of PVA (117, Kuraray Co., Ltd., Japan) were dissolved in 600ml of deionized water at 60°C, and stirred for 1h until completely dissolved. The viscous liquid was injected into a spherical mold with a diameter of 0.2cm, and dried in a vacuum drying oven at 80°C for 48h to remove the solvent. The product of Comparative Example 2 was obtained.

[0080] Comparative Example 3

[0081] The difference compared with Example 1 is that methanol vapor is not introduced in step 3 to obtain the product of Comparative Example 3. The SEM image of the product is as follows Figure 4 shown.

[0082] It can be seen from Comparative Example 3 that without the introduction of methanol vapor, the nucleation process of crystals in the solution cannot be promoted, which is not conducive to the generated grains, and therefore CD-MOF cannot be generated in situ by the solvothermal method. Such fragments will further reduce the mechanical properties of PVA itself and are not conducive to the slow release of nutrients.

[0083] Comparative Example 4

[0084] The difference compared with Example 1 is that the amount of surfactant added in step 3 is 0g, 400mg, and 1100mg to obtain product comparative examples 4A, 4B, and 4C.

[0085] It can be seen that surfactants play a key role in regulating the size of CD-MOF crystals. Figure 5 It can be seen from A that without adding surfactant, the CD-MOF crystal size is 128.3 μm, which is too large. When 400 mg of surfactant is added, Figure 5 As shown in B, the CD-MOF grain size dropped to 2.6 μm, which is too small. When the surfactant is added, the CD-MOF grain size can be adjusted to a suitable nanometer level (as shown in the embodiment). When the surfactant content is increased to 1100 mg, Figure 5 As shown in Figure C, the CD-MOF grain size aggregated to 2.4 μm.

[0086] Therefore, in the present invention, it is necessary to control the amount of added surfactant so as to adjust the CD-MOF grain size to the nanoscale, which has a positive effect on improving the mechanical strength, chemical stability and fertilizer utilization rate of PVA.

[0087] Experimental Example 1: Nutrient slow-release performance test

[0088] The nutrient slow-release performance of Examples 1-5 and Comparative Examples 1-4 was tested by the static water method. 2 g of the products of Examples 1-5 and Comparative Examples 1-4 were accurately weighed, sealed with a mesh bag, 100 ml of deionized water was added and sealed, and placed in a dark environment at room temperature. The total nitrogen and available potassium content of the solution after 5d, 15d, 30d, 45d, 60d, 75d, and 90d were tested by the Kjeldahl nitrogen determination method. The results are shown in Tables 1 and 2:

[0089] Table 1 Total nitrogen nutrient slow release performance of different samples

[0090]

[0091]

[0092] Table 2 Slow release performance of available potassium nutrients of different samples

[0093]

[0094] As can be seen from the data of total nitrogen and available potassium in Tables 1 and 2, the cumulative release of total nitrogen and available potassium in each embodiment gradually increased with the increase of the slow release time in Examples 1-4, and in Example 5 where potassium fertilizer was added alone, the cumulative release of total nitrogen was not detected, but the material was able to slowly release available potassium. Therefore, the nutrient content can be regulated by regulating the reactant ratio.

[0095] It can be seen from Comparative Example 1 that although the PVA material alone can be used to prepare a sustained-release material, no nutrients were detected.

[0096] From Comparative Example 2 in which water-soluble fertilizer and PVA were added separately, it can be seen that the material did not exhibit sustained-release performance because the water resistance of the PVA material itself was not effectively improved. Therefore, after 5 days in static water, the cumulative release of nutrients was very large.

[0097] In Comparative Example 3, because the in-situ CD-MOF with cavity structure was not formed, the added compound fertilizer was released rapidly in a short period of time and did not show a sustained release effect.

[0098] In products 4A-4C, the content of surfactant was changed, and the size of CD-MOF was effectively regulated from 128 μm to nanometer scale. Although micrometer-scale CD-MOF can also show a certain sustained release effect, the sustained release effect is not as significant as that of nanometer-scale CD-MOF in the embodiment, and micrometer-scale CD-MOF will affect the mechanical properties and dissolution weight loss rate of PVA.

[0099] Experimental Example 2: Dissolution Weight Loss Test

[0100] Weigh 2 g of each example and comparative example sample and soak it in 100 ml of deionized water for 12 hours, 24 hours, 36 hours, 48 ​​hours, and 72 hours, take it out regularly and dry it to constant weight, and weigh its mass M2 with an electronic balance, subtract the weight M1 before soaking, and calculate the dissolution weight loss rate of the material. The results are shown in Table 3.

[0101] Table 3 Dissolution weight loss rate of different samples

[0102]

[0103]

[0104] From Table 3, it can be seen that as the immersion time increases, the dissolution weight loss rate of the comparative example increases. This is because the PVA that has not undergone strength modification has poor water resistance and is not water-soluble, so the weight loss rate in water is too fast. In Comparative Example 3, since no crystal structure is produced, the water resistance of PVA cannot be improved. In Comparative Example 4, the components are relatively mechanically insufficient in the water resistance modification effect on PVA due to the relatively large size of CD-MOF. In each embodiment, the hydroxyl groups in cyclodextrin and the hydroxyl groups of PVA form a three-dimensional cross-linked structure through a hydrogen bond structure, which improves the water resistance and strength of PVA, thereby ensuring that PVA can swell in water without dissolving in water, absorbing and retaining a large amount of water. As the immersion time increases, the water absorbed by the PVA composite material causes the PVA to swell, and the dissolution weight loss rate increases and then decreases. The dissolution weight loss rates between the embodiments are much lower than those in the comparative examples, showing excellent sustained release properties.

[0105] Experimental Example 3: Determination of heavy metal adsorption and mechanical properties

[0106] Take soil contaminated by chromium at a concentration of 5 mg / g, take 2 g of each example and comparative example sample and bury it in the soil, and after leaving it for 30 days, detect the chromium (Cr) heavy metal content in the soil.

[0107] In order to well demonstrate the mechanical properties of the products of the embodiments and comparative examples, appropriate products were taken from each product before injection molding and films were made by the salivation film-forming method to test the mechanical properties of the products.

[0108] The method is as follows: first adjust the distance of the scraper of the coating device to 180-220 μm, then pour the static degassing liquid onto the glass plate, start the scraper coating, the coating speed is 3 m / min, and finally place the film in a vacuum oven at 80°C and dry it for 48 hours.

[0109] Mechanical properties test: Cut the PVA film into length × width = 15cm × 1cm, and clamp the film with the clamp of a universal testing machine to test the mechanical properties. The tensile strength of the film is measured using the national standard GB / T 1040.3-2006 Test of tensile properties of plastics Part 3 Test conditions for thin plastics and thin sheets. Repeat the test 5 times and calculate the average value.

[0110] The heavy metal and mechanical properties test results are shown in Table 4.

[0111] Table 4 Heavy metal adsorption performance of different samples

[0112]

[0113] It can be seen from the data in Table 4 that the PVA sustained-release material of the present invention has a good adsorption effect on heavy metal chromium in soil contaminated with heavy metal chromium. The mechanical properties of the PVA composite material in the embodiment of the present invention are improved compared with the comparative example, which also confirms the feasibility of the present invention. The crystal structure of the in-situ generated CD-MOF can effectively improve the mechanical properties of PVA and thus improve the sustained-release performance of the PVA material. The micron-structured CD-MOF formed in the comparative example cannot play a good role in improving the mechanical properties of PVA, which confirms the feasibility of the present invention.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A heavy metal adsorption slow-release fertilizer, which is composed of polyvinyl alcohol (PVA) and a cyclodextrin metal organic framework compound in situ grown on the polyvinyl alcohol (PVA), the cyclodextrin metal organic framework compound is composed of a complex formed by cyclodextrin and metal ions, and hydrogen bonds are formed between the polyvinyl alcohol and the cyclodextrin metal organic framework compound.

2. The heavy metal adsorption slow-release fertilizer according to claim 1, wherein: The mass ratio between the polyvinyl alcohol and the cyclodextrin in the cyclodextrin metal organic framework compound is 100:5-15.

3. The heavy metal adsorption slow-release fertilizer according to claim 1 or 2, wherein: The cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin (γ-CD); Preferably, the metal ion is a potassium ion.

4. A method for preparing the heavy metal adsorption slow-release fertilizer according to any one of claims 1 to 3, the method comprising the following steps: Step 1, dissolving water-soluble fertilizer and polyvinyl alcohol (PVA) in deionized water until they are completely dissolved to obtain a mixed aqueous solution of polyvinyl alcohol (PVA) containing water-soluble fertilizer; Step 2, dissolving cyclodextrin (e.g., γ-CD) in deionized water until it is completely dissolved to obtain a cyclodextrin aqueous solution; Step 3, mixing the solutions obtained in step 1 and step 2, and introducing methanol vapor to react to form a cyclodextrin metal-organic framework compound; Subsequently, a surfactant was added, stirred evenly, left to stand overnight, centrifuged, and the unreacted supernatant was removed to obtain a viscous liquid; Step 4, drying the viscous liquid obtained in step 3.

5. The method according to claim 4, wherein: In step 1, the water-soluble fertilizer is 10-30 parts, and the PVA is 100 parts by weight; Preferably, in step 1, the water-soluble fertilizer is 10-20 parts, and the PVA is 100 parts by weight; Preferably, in step 1, the temperature of the deionized water is 60-80°C; Preferably, step 1 also includes adjusting the pH value of the polyethylene (PVA) mixed aqueous solution containing water-soluble fertilizer to 4-6.

6. The method according to claim 4 or 5, wherein: In step 1, the water-soluble fertilizer is a mixed fertilizer of potash fertilizer and one or more fertilizers selected from fulvic acid, amino acid, humic acid, and alginic acid; Preferably, the potash fertilizer is selected from one or more of potassium nitrate, potassium sulfate, potassium dihydrogen phosphate, potassium chloride, potassium humate and amino acid potassium; Preferably, the mass ratio of the potash fertilizer to the one or more fertilizers selected from fulvic acid, amino acids, humic acid, and alginic acid is 1:0-5 parts.

7. The method according to any one of claims 4 to 6, wherein: In step 1, the mass fraction of the PVA in water is 15-30%, preferably 17-25%; Preferably, in step 1, the viscosity of the PVA is less than or equal to 32 mPa.s; Preferably, in step 1, the degree of polymerization of the PVA is 1700-2500; Preferably, in step 1, the hydrolysis degree of the PVA is 78-88%.

8. The method according to any one of claims 4 to 7, wherein: In step 2, the cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin (γ-CD); Preferably, in step 2, the cyclodextrin (such as γ-CD) is 5-15 parts, preferably 10-15 parts, relative to the mass fraction of the polyvinyl alcohol PVA in step 1; Preferably, in step 2, the temperature of the deionized water is 60-80°C, preferably 60°C.

9. The method according to any one of claims 4 to 8, wherein: In step 3, the amount of the surfactant added is 0.5-1 part relative to the mass fraction of the polyvinyl alcohol PVA in step 1; preferably, in step 3, the centrifugal speed is 2000-3000 r / min; Preferably, in step 3, the surfactant is a cationic surfactant selected from one or more of hexadecyltrimethylammonium bromide, hexadecylpolyoxyethylene ether dimethyloctyl ammonium chloride, ethylenebis[(octadecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(hexadecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(dodecylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(decylamidepropyl dimethyl) chloride / ammonium bromide], ethylenebis[(octylpolyoxyethylene / polyoxypropylene block group) ammonium chloride / (hexadecylpolyoxyethylene / polyoxypropylene block group) ammonium chloride], propylenebis[(hexadecylamidepropyl dimethyl) chloride / ammonium bromide] and propylenebis[(dodecylamidepropyl dimethyl) chloride / ammonium bromide].

10. The method according to any one of claims 4 to 9, wherein: In step 4, the drying temperature is 50-80°C.